Magnesium and Strontium compositions of pore fluids and bulk carbonates from Ocean Drilling Project Site 189-1171 - Piyali Chanda; Matthew S Fantle (PANGAEA, 2018)
The Mg and Sr isotopic compositions (d26Mg and87Sr/86Sr) of pore fluids and bulk carbonates from Ocean Drilling Project Site 1171 is located on the South Tasman Rise (48°29.996000S and 149°06.690100E) at a present-day waterdepth of 2148.2 m on a southwesterly dipping slope.
Supplement to: Chanda, P; Fantle, MS (2017): Quantifying the effect of diagenetic recrystallization on the Mg isotopic composition of marine carbonates. Geochimica et Cosmochimica Acta, 204, 219-239, https://doi.org/10.1016/j.gca.2017.01.010